Internalized weight bias mediates the relationship between depressive symptoms and disordered eating behavior among women who think they are overweight. (August 2016) - Sienko, Rachel M.; Saules, Karen K.; Carr, Meagan M.
Abstract: Objective: This study tested the potential mediating role of Internalized Weight Bias (IWB) in the relationship between depressive symptoms (DEP-SX) and disordered eating behavior. In particular, we hypothesized that IWB may be an intervening variable in the well documented association between depression and disordered eating. Method: College women (N = 172) who were taking undergraduate psychology courses and who endorsed thinking they were overweight completed the Patient Health Questionnaire depression screener (PHQ-9), the Weight Bias Internalization Scale (WBIS), and the Eating Disorder Examination Questionnaire (EDE-Q). Bootstrapping mediation analyses were conducted to explore the relationships between these variables. Results: IWB was significantly correlated with eating disorder symptoms and DEP-SX, but not Body Mass Index. Mediation analyses supported a model in which IWB mediated the relationship between DEP-SX and disordered eating behavior. Discussion: Results indicate that individuals with elevated DEP-SX may be likely to internalize weight bias, which may in turn lead to maladaptive approaches to eating and weight control, regardless of one's actual weight status. Highlights: Women who believe feel they are overweight risk are subject to internalization of weight bias (IWB). Depressive symptoms (DEP-SX) depression and disordered eating are associated with IWB. DEP-SX Depressive symptoms depression may set the stage for IWB, even among those who are not overweight. IWB mediates the relationship between DEP-SX depressive symptoms depression and disordered eating.